(untitled) (Journal of Parents and Teachers, 2017)
From one of the most studied infant disorders in the last century, it arises a possible intervention through innovative technique, the magic. It underlines the possibility to work from the magic and its tricks, it is going to be a reinforcement in that areas which children have more problems, and therefore, it makes more complex their learning process.